2021
DOI: 10.1155/2021/2252705
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Protective Effect of Luteolin on D‐Galactosamine (D‐Gal)/Lipopolysaccharide (LPS) Induced Hepatic Injury by in Mice

Abstract: To observe the effects of luteolin on galactosamine (D-Gal)/lipopolysaccharide (LPS) induced liver injury in mice. Male C57BL/6 mice were randomly divided into 4 groups: normal control group, D-GaI/LPS group, D-GaI/LPS + luteolin (Lu, 20 mg/kg), and D-GaI/LPS + luteolin (Lu, 40 mg/kg). Mice in the normal control group and D-GaI/LPS group were given distilled water while other groups were given drugs in 7 days by gavage. 4 hours after the continuous administration, Gal (700 mg/kg) and LPS (10 mg/kg) were inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…Current research supports several earlier reports that have shown that LPS induces hepatic damage, and therefore increases the concentrations of the aminotransferases (ALT, AST, ALP, and GGT) [11,[28][29][30][31][32][33]. The hepatic enzymes are cytoplasmic, and alteration in the membrane permeability will cause dysfunction and damaged structural integrity of hepatocytes and the aminotransferases to leak to the bloodstream, thereby resulting in an increase of the aminotransferases in the plasma of the male and female rat models, characterized by viral hepatitis, diabetes, heart failure, bile duct problems, haemorrhage, inflammation, cardiac, muscular, biliary, and injury, and microabscess formation, activation of the transcription factor nuclear factor-kappa B, and many inflammatory genes [11,27,28,30,33,[34][35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…Current research supports several earlier reports that have shown that LPS induces hepatic damage, and therefore increases the concentrations of the aminotransferases (ALT, AST, ALP, and GGT) [11,[28][29][30][31][32][33]. The hepatic enzymes are cytoplasmic, and alteration in the membrane permeability will cause dysfunction and damaged structural integrity of hepatocytes and the aminotransferases to leak to the bloodstream, thereby resulting in an increase of the aminotransferases in the plasma of the male and female rat models, characterized by viral hepatitis, diabetes, heart failure, bile duct problems, haemorrhage, inflammation, cardiac, muscular, biliary, and injury, and microabscess formation, activation of the transcription factor nuclear factor-kappa B, and many inflammatory genes [11,27,28,30,33,[34][35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…The liver prevents bacteria and endotoxins from entering the systemic circulation by removing them from the portal venous blood (Dhainaut et al, 2001; Srivastava & Gimson, 2013). During sepsis, the NLRP3 inflammasome is activated by LPS and mediates maturation of excess inflammatory cytokines, resulting in progression of ALI (Pu, Yang, & Mo, 2021; Wang et al, 2021). However, mice deficient in NLRP3 are completely resistant to LPS‐induced inflammation and liver injury (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being involved in various stages of metabolic diseases, such as T2DM and NAFLD, inflammatory cytokines, such as IL6 and IL1B, contribute to IR by activating phosphatases that provide negative feedback to the insulin signaling cascade. Notably, significant inhibitory effects of luteolin on various inflammatory factors, including IL6 and IL‐1β, were reported in multiple disease models (Kou et al, 2022; Liu et al, 2022; Pu et al, 2021). The activation of VEGFA is strongly associated with the levels of oxidative stress, and VEGFA modulation can be effective in mitigating and preventing damage caused by oxidative stress (Hepp et al, 2021).…”
Section: Discussionmentioning
confidence: 99%